Insulin Resistance Exacerbates Genetic Predisposition to Nonalcoholic Fatty Liver Disease in Individuals Without Diabetes. Issue 7 (18th April 2019) - Barata, Llilda; Feitosa, Mary F.; Bielak, Lawrence F.; Halligan, Brian; Baldridge, Abigail S.; Guo, Xiuqing; Yerges‐Armstrong, Laura M.; Smith, Albert V.; Yao, Jie; Palmer, Nicholette D.; VanWagner, Lisa B.; Carr, J. Jeffrey; et al.
Abstract : The accumulation of excess fat in the liver (hepatic steatosis) in the absence of heavy alcohol consumption causes nonalcoholic fatty liver disease (NAFLD), which has become a global epidemic. Identifying metabolic risk factors that interact with the genetic risk of NAFLD is important for reducing disease burden. We tested whether serum glucose, insulin, insulin resistance, triglyceride (TG), low‐density lipoprotein cholesterol, high‐density lipoprotein cholesterol, body mass index (BMI), and waist‐to‐hip ratio adjusted for BMI interact with genetic variants in or near the patatin‐like phospholipase domain containing 3 ( PNPLA3 ) gene, the glucokinase regulatory protein ( GCKR ) gene, the neurocan/transmembrane 6 superfamily member 2 ( NCAN/TM6SF2 ) gene, and the lysophospholipase‐like 1 ( LYPLAL1 ) gene to exacerbate hepatic steatosis, estimated by liver attenuation. We performed association analyses in 10 population‐based cohorts separately and then meta‐analyzed results in up to 14, 751 individuals (11, 870 of European ancestry and 2, 881 of African ancestry). We found that PNPLA3‐ rs738409 significantly interacted with insulin, insulin resistance, BMI, glucose, and TG to increase hepatic steatosis in nondiabetic individuals carrying the G allele. Additionally, GCKR‐ rs780094 significantly interacted with insulin, insulin resistance, and TG. Conditional analyses using the two largest European ancestry cohorts in the study showed that insulin levels accounted for most of the interaction of PNPLA3‐ rs738409 with BMI, glucose, and TG in nondiabetic individuals. Insulin, PNPLA3 ‐rs738409, and their interaction accounted for at least 8% of the variance in hepatic steatosis in these two cohorts. Conclusion: Insulin resistance, either directly or through the resultant elevated insulin levels, more than other metabolic traits, appears to amplify the PNPLA3 ‐rs738409‐G genetic risk for hepatic steatosis. Improving insulin resistance in nondiabetic individuals carrying PNPLA3‐ rs738409‐G may preferentially decrease hepatic steatosis. Abstract :